The origins of submissive compassion: the traumatic impact of early shame experiences, shame, self-criticism and social anxiety - Martins, Dinis Rafael dos Santos (2019)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação